Micro EEG/ECG signal's chopper-stabilization amplifying chip for novel dry-contact electrode *Project supported by the National Natural Science Foundation of China (Nos. 61527815, 31500800, 61501426, 61471342), the National Key Basic Research Plan (No. 2014CB744600), the Beijing Science and Technology Plan (No. Z141100000214002), and the Chinese Academy of Sciences' Key Project (No. KJZD-EW-L11-2). (February 2017) - Sun, Jianhui; Wang, Chunxing; Wang, Gongtang; Wang, Jinhui; Hua, Qing; Cheng, Chuanfu; Cai, Xinxia; Yin, Tao; Yu, Yang; Yang, Haigang; Li, Dengwang
Abstract: Facing the body's EEG (electroencephalograph, 0.5–100 Hz, 5–100 μ V) and ECG's (electrocardiogram, < 100 Hz, 0.01–5 mV) micro signal detection requirement, this paper develops a pervasive application micro signal detection ASIC chip with the chopping modulation/demodulation method. The chopper-stabilization circuit with the RRL (ripple reduction loop) circuit is to suppress the ripple voltage, which locates at the single-stage amplifier's outputting terminal. The single-stage chopping core's noise has been suppressed too, and it is beneficial for suppressing noises of post-circuit. The chopping core circuit uses the PFB (positive feedback loop) to increase the inputting resistance, and the NFB (negative feedback loop) to stabilize the 40 dB intermediate frequency gain. The cascaded switch-capacitor sample/hold circuit has been used for deleting spike noises caused by non-ideal MOS switches, and the VGA/BPF (voltage gain amplifier/band pass filter) circuit is used to tune the chopper system's gain/bandwidth digitally. Assisted with the designed novel dry-electrode, the real test result of the chopping amplifying circuit gives some critical parameters: 8.1 μ W/channel, 0.8 μ Vrms (@band-width = 100 Hz), 4216–11220 times digitally tuning gain range, etc. The data capture system uses the NI CO's data capturing DAQmx interface, and the captured micro EEG/ECG's waves are real-time displayed with the PC-Labview. The proposed chopper system is a unified EEG/ECG signal's detection instrument and has a critical real application value.